The Effect of Cellular Redox Status on the Evolvability of New Catabolic Pathways - Maia Kivisaar (American Society for Microbiology, 2018)
ABSTRACT Oxidation of aromatic compounds can be mutagenic due to the accumulation of reactive oxygen species (ROS) in bacterial cells and thereby facilitate evolution of corresponding catabolic pathways. To examine the effect of the background biochemical network on the evolvability of environmental bacteria hosting a new catabolic pathway, Akkaya and colleagues (mBio 9:e01512-18, 2018, https://doi.org/10.1128/mBio.01512-18) introduced the still-evolving 2,4-dinitrotoluene (2,4-DNT) pathway genes from the original environmental Burkholderia sp. isolate into the genome of Pseudomonas putida KT2440. They show that the mutagenic effect of 2,4-DNT oxidation, which is associated with the accumulation of ROS and oxidative damage on DNA, can be avoided by preserving high NADPH levels in P. putida. The observations of this study highlight the impact of the cellular redox status of bacteria on the evolvability of new metabolic pathways.